Analytically continued fock space multi-reference coupled-cluster theory: application to the shape resonance - Pal, Sourav; Sajeev, Y.; Vaval, Nayana (Chemical Physics, 2006)
The Fock space multi-reference coupled-cluster (FSMRCC) method is used for the study of the shape resonance energy and width in an electron-atom/molecule collision. The procedure is based upon combining a complex absorbing potential (CAP) with FSMRCC theory. Accurate resonance parameters are obtained by solving a small non-Hermitian eigen-value problem. We study the shape resonances in e(-)-C2H4 and e(-)-Mg. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: complex absorbing potential; correlated independent particle potential; Fock space multi-reference coupled-cluster theory; shape resonance

Ab initio and periodic DFT investigation of hydrogen storage on light metal-decorated MOF-5 - Dixit, Mudit; Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2011)
The effect of light metal (M = Li, Be, Mg, and Al) decoration on the stability of metal organic framework MOF-5 and its hydrogen adsorption is investigated by ab initio and periodic density functional theory (DFT) calculations by employing models of the form BDC:M-2:nH(2) and MOF-5:M-2:nH(2), where BDC stands for the benzenedicarboxylate organic linker and MOF-5 represents the primitive unit cell. The suitability of the periodic DFT method employing the GGA-PBE functional is tested against MP2/6-311 + G* and MP2/cc-pVTZ molecular calculations. A correlation between the charge transfer and interaction energies is revealed. The metal-MOF-5 interactions are analyzed using the frontier molecular orbital approach. Difference charge density plots show that H-2 molecules get polarized due to the charge generated on the metal atom adsorbed over the BDC linker, resulting in electrostatic guest-host interactions. Our solid state results show that amongst the four metal atoms, Mg and Be decoration does not stabilize the MOF-5 to any significant extent. Li and Al decoration strengthened the H-2-MOE-5 interactions relative to the pure MOF-5 exhibited by the enhanced binding energies. The hydrogen binding energies for the Li- and Al-decorated MOF-5 were found to be sensible for allowing reversible hydrogen storage at ambient temperatures. A high hydrogen uptake of 4.3 wt.% and 3.9 wt.% is also predicted for the Li- and Al-decorated MOF-5, respectively. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ab initio calculations; Density functional theory; Hydrogen binding energies; Hydrogen storage; Metal-Pi-Arene interactions

Auger decay rates of core hole states using equation of motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2017)
The recent development of Linac coherent light source high intense X-ray laser makes it possible to create double core ionization in the molecule. The generation of double core hole state and its decay is identified by Auger spectroscopy. The decay of this double core hole (DCH) states can be used as a powerful spectroscopic tool in chemical analysis. In the present work, we have implemented a promising approach, known as CAP-EOMCC method, which is a combination of complex absorbing potential (CAP) and equation -of-motion coupled cluster (EOMCC) approach to calculate the lifetime of single and double core hole states. We have applied this method to calculate the lifetime of the single core hole (K-LL) and double core hole (KK-KLL) states of CH4, NH3 and HF molecules. The predicted lifetime is found to be extremely short. (C) 2016 Elsevier B.V. All rights reserved.

Aluminum cluster for CO and O-2 adsorption - Samanta, Bipasa; Sengupta, Turbasu; Pal, Sourav (Journal of Molecular Modeling, 2019)
Low temperature oxidation of CO to CO2 is an important process for the environment. Similarly adsorption of CO from the releasing sources is also of major concern today. Whereas the potential of gold and silver clusters is well proven for thecatalysis of the above mentioned reaction, the potential of aluminum (Al) clusters remains unexplored. The present study proves that, similar to the transition metals, Al clusters can also be used for adsorption of gases. We first tested the potential of Al cluster as adsorbents for CO. The high binding energy (BE) values prove that Al clusters can be used for adsorbing both CO and O-2. Since oxygen binding is more facile, we adsorbed oxygen on Al and then checked the effect of this O-2 on the BE of CO. The results were obtained by DFT calculations at M062X/TZVP level of theory.
Keywords: Aluminum clusters; Charge decomposition analysis; CO adsorption; DFT; O-2 adsorption; Wiberg bond indices